Pulmonary Infections in Patients with Human Immunodeficiency Virus Infection - Cilloniz, Catia; Pericàs, Juan M.; Miró, José M.; Torres, Antoni (Seminars in Respiratory and Critical Care Medicine, 2025)
Pulmonary infection is an important cause of hospitalization, morbidity, and mortality in people living with human immunodeficiency virus (HIV; PWH) infection, especially in those with significant immunosuppression. Pneumonia, including Pneumocystis jirovecii and Mycobacterium tuberculosis etiologies, continues to be the most frequent pulmonary infection in PWH. However, identifying the etiology of pulmonary infection in PWH is challenging because of the overlap in clinical features and the frequency of co-infection. This review focuses on the current scientific evidence regarding pulmonary infection in PWH, including its epidemiology, clinical presentation, diagnosis, and management.
Keywords: pulmonary infection; human immunodeficiency virus; antiretroviral therapy